Evaluating the introduction of Scottish Gaelic public broadcaster BBC Alba - Willis, Craig (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
The article evaluates the policy decision to introduce BBC Alba and provide a public service for Gaelic speakers, focusing on the differing aims and mandates of its two funders – the BBC and MG Alba. Using a logical framework, we examine the aims and strategy BBC Alba has deployed in the context of its two main audience groups: the core Gaelic community and the wider Scottish audience. We utilise data from annual reports, including audience size, number of online streamers, and audience satisfaction. Our analysis suggests that while the stated aims have largely been achieved, the original aims were skewed towards the wider community rather than contributing to language maintenance/ revitalisation. We offer suggestions on how the inputs and outputs could be tweaked to improve the policy’s impact on Gaelic speakers. We conclude that the impact of BBC Alba has been more successful with the wider Scottish audience than the core Gaelic community.
Keywords: javna radiotelevizija; manjšinski jeziki; minority languages; policy evaluation; presoja politike; public broadcasting; Scottish Gaelic; škotska gelščina